The dynamics of local learning in global value chains :experiences from East Asia - Kawakami, Momoko.; Sturgeon, Timothy J. (IDE-JETRO series., 2011)
"This book investigates the process and mechanism of the capability development of East Asian local manufacturers, which has underpinned their phenomenal rise in the worlds competitive landscape of industrial production during the last few decades"--Provided by publisher.